The accessibility of workplace built environment to the disabled employees in Malaysia - Hashim, Junaidah; Wok, Saodah; Abdul Rahim, Asiah (2011)
The study examines various aspects of workplace built environment provided by the employers in Malaysia to their disabled employees. The assessment is gauged by the disabled employees personally, based on the contributions of the employing organisation, in relation to organisation contributions for the disabled employees, the facilities provided, the accessibility of the facilities provided, and their level of satisfaction with the condition of the provided facilities. The study employs survey research design using questionnaire as the tool for data collection. The 387 respondents were from Selangor, Kuala Lumpur, Putrajaya, Kelantan, Kedah, Pulau Pinang, and Johor. Data were analysed using descriptive statistics whereby the frequency, percentage, means and standard deviations are presented.